(untitled) (International Journal of Engineering and Computer Science, 2014)
The bowtie antenna with two types of feed structure is analyzed in this paper. The co-planar waveguide (CPW) fed bowtie antenna is compared with the asymmetric co-planar stripline (ACS) fed bowtie antenna on the parameters like return loss characteristics and frequency bandwidth percentage. The antenna is designed using the software CADFEKO 5.5 suit and the results are analyzed. The results show that Bowtie antenna with CPW feed gives good bandwidth enhancement and Bowtie antenna with ACS feed gives good impedance matching for the wireless applications.